Managing dual-career families: An Islamic framework for family harmony and resilience - St. Sariroh; Moh. Ali; Abd. Syakur (An-Nisa’ Journal of Gender Studies, 2023)
The phenomenon of dual-career couples presents significant challenges in balancing work demands, domestic responsibilities, childcare, and family harmony. This study aims to develop a conceptual framework for managing dual-career families by integrating women’s multidimensional roles, spouses' shared responsibilities, and Islamic principles to enhance family harmony and resilience. The study employs a qualitative approach through a literature review. Data were purposively drawn from academic literature, Islamic sources, and family-related regulations and were analyzed descriptively and qualitatively through source identification, categorization, comparison, interpretation, and synthesis. The findings indicate that, from an Islamic perspective, the management of dual-career families rests on integrating domestic, professional, economic, and relational roles through spousal cooperation. The proposed framework comprises five key dimensions: a shared vision, relational harmony, childcare, financial management, and a balance between rights and responsibilities. These dimensions are reinforced by eight Islamic principles: planning, adherence to religious boundaries, mutual consent, ma‘ruf (fair and appropriate conduct), nihlah (sincere giving), ihsan (benevolence), shura (mutual consultation), and islah (reconciliation). The study demonstrates that the resilience of dual-career families can be strengthened through cooperative role-sharing, effective communication, mutual consultation, conflict management, and a balanced approach to career and family demands. Theoretically, this study extends the literature on family management and work–family conflict by incorporating Islamic moral, spiritual, and relational dimensions into a framework for managing dual-career families. In practice, the framework provides a foundation for couples and relevant institutions to promote co-parenting, flexible work arrangements, and family counseling.